2016
DOI: 10.21162/pakjas/16.5559
|View full text |Cite
|
Sign up to set email alerts
|

DIVERSITY IN PHYTOCHEMICAL COMPOSITION OF OMANI FENUGREEK (Trigonella foenum - graecum L.) ACCESSIONS

Abstract: Trigonella foenum-graecum L. is an annual dicotyledonous plant, which belongs to the subfamily Papilionaceae of the Leguminaceae family (Acharya et al., 2006b). Historically, it has always been known as a medicinal herb for over two thousand years in various parts of the world (Srinivasan, 2006;Raja and Kudesia, 2012). Due to its distinct smell, it was described as a 'malodorous' plant (Pour et al., 2012;Lust, 2014). It imparts a pleasant flavour, colour and aroma to foods that make it a highly desirable suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
1
6
1
Order By: Relevance
“…The tannins content recorded for aqueous extracts of fenugreek seeds was better, compared to that recorded in the works of Al-Maamari et al [35] for the same species that have found a tannin content of 0.78%, this difference is probably due to the soil composition. Tannins are substances of organic origin that are found in all parts of the plant [36], those are proton donors to free radicals produced during peroxidation allowing cessation of auto-oxidation reaction [37].…”
Section: Total Alkaloidscontrasting
confidence: 73%
“…The tannins content recorded for aqueous extracts of fenugreek seeds was better, compared to that recorded in the works of Al-Maamari et al [35] for the same species that have found a tannin content of 0.78%, this difference is probably due to the soil composition. Tannins are substances of organic origin that are found in all parts of the plant [36], those are proton donors to free radicals produced during peroxidation allowing cessation of auto-oxidation reaction [37].…”
Section: Total Alkaloidscontrasting
confidence: 73%
“…Yimam et al 24 also recorded the significant (p < 0.05) difference among T. foenum-graecum genotypes for most of the agro-morphological traits examined in Ethiopia as the second most diverse country. The quantitative and qualitative traits of the studies AEPs of fenugreek are in agreement with previous investigations from other countries 23 , 25 29 . In a study, the seed number per pod, pod number per plant, and 1000 seed weight were measured as 13.6, 5.7, and 7.3 g for the samples collected from Miandoab, Urmia province in Iran, respectively 30 .…”
Section: Resultssupporting
confidence: 91%
“…Our results revealed that the phenolic and flavonoid components were remarkably contributed to the antioxidant property of fenugreek. The other researchers have also declared a positive and significant association between antioxidant activity and the plant total phenol and total flavonoid conten 54 , 58 , 59 . Himalian and Singh 60 reported that flavonoids increase the antioxidant activity of the plant.…”
Section: Resultsmentioning
confidence: 93%
“…This is also supported by the moderate levels of genetic differentiation among the 33 cultivars and accessions, indicating that the level of gene flow is low among the cultivars. Previous studies have shown that populations with limited outcrossing tend to having a low level of genetic diversity and a moderate to high level of genetic differentiation (Al-Sadi et al 2012;Al-Maamari et al 2014;Gannibal et al 2014;Al-Sadi et al 2015). However, it has been reported that there was a range of polymorphism (41-70%) in mandarin analyzed by AFLP which suggested the possibility of having diverse type of mandarins within the accessions examined (Dorji & Yapwattanaphun 2015).…”
Section: Discussionmentioning
confidence: 88%
“…AFLP fingerprinting proved to be powerful in grouping citrus cultivars according to their level of relatedness to each other. AFLP is a widely used technique in the population genetic and phylogenetic studies of plants and microorganisms (Keivani et al 2010;Al-Sadi et al 2012;Kumar et al 2012 (Nei 1978) of 12 citrus species and 6 accessions based on AFLP fingerprinting analysis using 910 polymorphic loci Casasnovas et al 2013;Al-Maamari et al 2014;Al-Sadi et al 2015). AFLP is also commonly used for studying relationship and genetic diversity in citrus species (Nartvaranant & Nartvaranant 2011;Khiavi et al 2015;Zhou et al 2017).…”
Section: Discussionmentioning
confidence: 99%